The Influence of Psychological Capital on Career Anxiety of Students of the Faculty of Tarbiyah and Teacher Training UIN Malang - Sari Amalia, Rahmatika; Putri Ayuningsih, Apreta (Rifa'Institute, 2025)
Introduction: Career anxiety is frequently experienced by final-year students as they face uncertainties in entering the workforce. An initial survey of eighth-semester Faculty of Tarbiyah and Teacher Training students at UIN Malang and Tracer Study data (2023) indicate high levels of career anxiety and long job waiting periods. Objective: This study aims to analyze the effect of psychological capital on career anxiety among eighth-semester Faculty of Tarbiyah and Teacher Training students, class of 2021. Method: A quantitative cross-sectional design was used with purposive sampling involving 100 respondents. Data were collected through a Likert-scale survey using the Career Anxiety Scale and the Psychological Capital Questionnaire. Data were analyzed using multiple linear regression. Result & Discussion: Psychological capital showed a significant negative effect on career anxiety (p = 0.000). Higher psychological capital—self-efficacy, hope, optimism, and resilience—reduced students' career anxiety, highlighting its role in supporting students' readiness for the workforce. Conclusion: Psychological capital is an essential predictor of career anxiety and should be strengthened through institutional support program